Task scheduling algorithm for distributed environment based on signal-driven - Yu XIN; Jing YANG; Zhi-qiang XIE (Tongxin xuebao)
In order to optimize the performance of user services in IaaS,the task scheduling algorithm for IaaS based on signal-driven is proposed,by which CS(control subsystem) and NS(inquiry nodes subsystem) based on the structural characteristics of the IaaS is established,and the DAG scheduling model based on the structural characteristics of the inquiry task is created.Then the conversion mechanism for the task partitions is created,constructing the signal communication mechanism for CS and NS,changing the status of the task partitions by signal-driven between the CS and NS,completing the task partitions allocation by POSS (parallel optimization selective strategy) in the scheduling time.This algorithm with low complexity is compatible with the distributed architecture of IaaS,because of utilizing dual system control mode.The effectiveness and practicality of this algorithm is verified by experiment.